2007
DOI: 10.1016/j.peptides.2007.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Chronic caloric restriction induces forestomach hypertrophy with enhanced ghrelin levels during aging

Abstract: Caloric restriction (CR) is the only preventive intervention that has robust pro-longevity effects in experimental models. Various circulating hormones that regulate the state of negative energy balance may drive the multi-system beneficial effects of the CR phenomenon. Ghrelin, one such stomach-derived circulating peptide hormone stimulates food intake, promotes GH release and inhibits pro-inflammatory cytokines. We have recently demonstrated that ghrelin also reverses agerelated thymic involution. Here, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 34 publications
3
30
1
Order By: Relevance
“…In line with previous reports showing that plasma ghrelin levels [16] and production of ghrelin in the stomach [17] rise after DR in WT mice, we have shown that 3 months of DR increases protein levels of gastric ghrelin. We also found that hippocampal ghrelin expression was increased in WT mice maintained on DR regimen.…”
Section: Disclosure Summarysupporting
confidence: 93%
See 1 more Smart Citation
“…In line with previous reports showing that plasma ghrelin levels [16] and production of ghrelin in the stomach [17] rise after DR in WT mice, we have shown that 3 months of DR increases protein levels of gastric ghrelin. We also found that hippocampal ghrelin expression was increased in WT mice maintained on DR regimen.…”
Section: Disclosure Summarysupporting
confidence: 93%
“…These findings indicate that certain factors or hormones, which are increased during DR, may be responsible for the beneficial effects of DR. Considering that plasma ghrelin levels rise significantly during DR [16,17], this peptide hormone may be a potential mediator of enhancement of hippocampal neurogenesis induced by DR. However, it is still unclear whether ghrelin is involved in DR-induced hippocampal neurogenesis.…”
Section: Image Processingmentioning
confidence: 99%
“…20 Interestingly, intrathymic ghrelin expression declines with age and is associated with age-related thymic involution. 12 Thus the reduction of T cell-derived ghrelin in a tissue microenvironment may play a role in regulating the inflammatory cytokines.…”
Section: Age-related Reduction In Ghrelin Expression and Inflammationmentioning
confidence: 99%
“…These findings and the observations that circulating ghrelin levels are increased prior to a meal and during food deprivation and caloric restriction, as well as in disease states such as anorexia and cachexia, but reduced after a meal and in obesity (Ikezaki et al 2002;Liu et al 2008;Shiiya et al 2002;Tschop et al 2001aTschop et al , 2001bVan der Lely et al 2004;Yang et al 2007), strongly implicate ghrelin being involved in the regulatory processes controlling meal initiation, priming metabolic pathways and leading to more efficient calorie storage.…”
Section: Page 5 Of 37mentioning
confidence: 93%